A Translation Analysis Of Noun Phrase In Happily Ever After Into Bahagia Selamanya Novel By Elliyanti Jacob Saleh - Kusindarti, Yunita; , Dr. Dwi Haryanti, M.Hum; , Mauly Halwat Hikmat, Ph. D (2015)
The aims of this research are to classify the translation shift of noun phrase and to describe the equivalent translation of noun phrase in the novel Happily Ever After by Julia Quinn into Bahagia Selamanya by Elliyanti Jacob Saleh. The type of this research is descriptive qualitative research. The subject of research is Happily Ever After novel by Julia Quinn into Bahagia Selamanya novel by Elliyanti Jacob Saleh and the object of research is noun phrase in Happily Ever After novel by Julia Quinn into Bahagia Selamanya novel by Elliyanti Jacob Saleh. The researcher uses documentation in collecting data and uses comparative method to analyze the data. The results of research paper show that: 1) The translation shift is divided into 2 types, they are level shift and structure shift. From 469 data, the researcher finds 400 data or 85% of noun phrase belong to level shift and 69 data or 15% belong to structure shift. There are two types of noun phrase, namely English noun phrase and Indonesian noun phrase. English noun phrase divided into ten types, they are NP1, NP2, NP3, NP4, NP5, NP6, NP7, NP8, NP9, NP and NP10. Indonesian noun phrase is divides into ten types, they are NPa, NPb, NPc, NPd, NPe, NPf, NPg, NPh, NPi, and NPj. In level shift, the researcher finds two types of noun phrase, they are NP1 and NP3. In NP1, there are NP1 which are translated into noun that has 356 data or 76%, NP1 which are translated into verb that has 21 data or 4,5%, and NP1 which are translated into adjective that has 14 data or 3%. In NP3, there are NP3 which are translated into noun that has 6 data or 1,3%, NP3 which are translated into verb that has 2 data or 0,4%, and NP3 which are translated into adjective that has 1 data or 0,2%. While, in structure shift the researcher finds four types of noun phrase, they are NP1, NP3, NP6, and NP7. In NP1, there are NP1 which are translated into adverb phrase that has 3 data or 0,6%, NP1 which are translated into NPa that has 8 data or 1,7%, NP1 which are translated into NPc that has 1 data or 0,2%, NP1 which are translated into NPe that has 3 data or 0,6%, and NP1 which are translated into NPf that has 20 data or 4,2%. In NP3, there are NP3 which are translated into NPa that has 7 data or 1,5%, NP3 which are translated into NPc that has 14 data or 3%, and NP3 which are translated into NPi that has 9 data or 1,9%. In NP, there are NP6 which are translated into verb phrase that has 1 data or 0,2%, NP6 which are translated into adjective phrase that has 1 data or 0,2%, and NP6 which are translated into adverb phrase that has 1 data or 0,2%. The last type is NP7 which are translated into NPc that has 1 data or 0,2%. 2) The equivalence of translation is divided into equivalent translation and non equivalent translation. All of data found by researcher is equivalence. It means that 469 data or 100% data are equivalence.